WORD ASSOCIATION RESPONSES IN RELATION WITH LEXICAL STORAGE OF STUDENTS IN INDONESIA INTERACTIVE STANDARD SCHOOL (IISS) MALANG - SARI, NUR ATIKAH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: word association test, lexical storage, mental lexicon, bilingualchildren Word association test is a test used to investigate lexical storage in mental lexicon. In this test, the participants are asked to respond to the first words come into their minds right after they are given the stimulus words. By doing this test, the writer aimed to find out the types of word association produced by students in Indonesia Interactive Standard School (IISS) Malang and to what extent Indonesian and local languages influence students’ responses in Indonesia Interactive Standard School (IISS) Malang. The theories used to achieve the purpose of this study are Field’s (2004) and Lawson’s (2007) about word association test and lexical storage of L2 learners. The participants of this study were 45 students of IISS. Then, the data of this study were students’ responses obtained by having word association test.The result showed that encyclopaedic association was the most type found in the students’ responses with 135 responses (38.8%). Then, syntagmatic association had 114 responses (2.8%) comprising collocation with 80 responses (23%) and multi word items with 34 responses (9.8%). Meanwhile, paradigmatic association had total 56 responses (16.1%) in which antonym were 19 responses (5.5%), synonym were 2 responses (0.6%), superordinate were 5 responses (1.4%), co-ordinate were 14 responses (4%), and meronymy were 16 responses (4.6%). Then, 13 students made responses which were categorized in misunderstanding due to homophone and it resulted in 13 responses (3.7%). Moreover, based on the result found, Indonesian language still influenced the students in responding the stimulus words even though the responses appeared only 22 responses (6.3%) of 352 responses found. However, local languages did not influence the responses. In conclusion, bilingual children tend to associate words by chain relationship and their first language  still influences the responses.The writer suggests to Study Program of English to provide more studies or references in psycholinguistics field, especially about lexical storage. Then, the writer also suggests for the next writers who want to conduct research in the same topic to take different participants and categorization of word association types.